Regio- and stereoselective selenium dioxide allylic oxidation of (E)-dialkyl alkylidenesuccinates to (Z)-allylic alcohols: synthesis of natural and unnatural butenolides - Patel, Ramesh M.; Puranik, Vedavati G.; N. P. Argade (Organic & Biomolecular Chemistry, 2011)
The first SeO(2) induced (Z)-selective allylic alcohol formation of dialkyl alkylidenesuccinates has been demonstrated to accomplish one-step syntheses of several essential butenolides and fused butenolides via an unusual E- to Z- carbon-carbon double bond isomerisation followed by the lactonization pathway. The observed regio- and stereoselective SeO(2) allylic oxidation protocol has also been extended to the diastereoselective total synthesis of bioactive natural product isomintlactone, its direct conversion to mintlactone and an example of the base-catalyzed intramolecular rearrangement of gamma-lactone to delta-lactone.